Digital anaesthesia: one injection or two?. Issue 7 (1st April 2010) - Cannon, Beverley; Chan, Louisa; Rowlinson, Joanna S; Baker, Matthew; Clancy, Mike
Abstract : Background: Digital nerve blocks (DNB) are performed frequently in the Emergency Department (ED). The aim of this study was to establish whether single injection subcutaneous digital nerve block (SDNB) is as effective as the traditional (two injection) digital nerve block (TDNB) for digital anaesthesia. Method: Single blinded, prospective, randomised-controlled multicentre trial within Hampshire EDs. Patients ≥16 years attending the ED with fingertip injuries/infections (distal to the distal-interphalangeal joint) requiring a DNB were randomised to SDNB/TDNB groups. Outcome measures were: primary - successful anaesthesia; secondary - patient distress, clinician satisfaction (CS), complications. Results: 76 patients were randomised. (37 received SDNB). At 5 min, more patients in the SDNB group (28/37, 76%) were adequately anaesthetised than in the TDNB group, (22/34, 65%). At 10 min, 33/37 (89%) of the SDNB group compared to 28/34 (82%) of the TDNB group were adequately anaesthetised. The mean (SD) of self-reported distress scores for the SDNB group were lower than those reported for the TDNB group, whereas the mean (SD) of CS scores for SDNB were higher than those reported for TDNB. Neither group reported complications from anaesthesia. Conclusions: SDNB is as effective as TDNB. Outcome measures favoured SDNB, but only CS scores achieved statistical significance. Trial recruitment is much slower than anticipated. However, clinical practice has demonstrated that SDNB works and practice is already changing within the Hampshire region, with some departments adopting SDNB as standard practice. Therefore, the results are being presented now to allow clinicians to make an informed choice. Our results may also contribute to future metanalyses.